Cerebral infarction: diagnosis and assessment of prognosis by using 123IMP-SPECT and CT. - Hayman, L A; Taber, K H; Jhingran, S G; Killian, J M; Carroll, R G (American Journal of Neuroradiology, 1989)
A multicenter prospective study was performed in 49 patients with 77 regions of cerebral infarction. Each patient was evaluated in the acute (0-5 days) and subacute (6-17 days) phases by (1) clinical neurologic examination, (2) CT scans, and (3) N-isopropyl-p-123I-iodoamphetamine (123IMP) single-photon emission CT (SPECT) scans. The abilities of the scans to (1) detect a lesion and (2) predict the clinical outcome were assessed. For lesion detection, 123IMP-SPECT was superior to CT in the first 2 days, but the scans were equally effective 3-5 days after onset. In the subacute phase, IV contrast-enhanced CT was superior to 123IMP-SPECT and unenhanced CT. The clinical outcome was only mildly correlated with the results of the acute and subacute 123IMP-SPECT and the acute CT scans. Reduction in lesion size on the subacute scans did not correlate with clinical improvement. We conclude that the parameters measured by CT and 123IMP-SPECT in patients with acute cerebral infarction cannot reliably be used to predict clinical outcome. 124I contamination of 123IMP and the use of low-energy collimators may have decreased lesion detectability.